How far to the promised land eaudiobook One black family's story of hope and survival in the american south. - McCaulley, Esau (Books on Tape, 2023)
From the New York Times contributing opinion writer and award-winning author of Reading While Black, a riveting intergenerational account of his family’s search for home and hope “Powerful . . . McCaulley uses examples of his own family’s stories of survival over time to remind readers that some paths to the promised land have detours along the way.”— The Root A PUBLISHERS WEEKLY BEST BOOK OF THE YEAR For much of his life, Esau McCaulley was taught to see himself as an exception: someone who, through hard work, faith, and determination, overcame childhood poverty, anti-Black racism, and an absent father to earn a job as a university professor and a life in the middle class.   But that narrative was called into question one night, when McCaulley answered the phone and learned that his father—whose absence defined his upbringing—died in a car crash. McCaulley was being asked to deliver his father’s eulogy, to make sense of his complicated legacy in a country that only accepts Black men on the condition that they are exceptional, hardworking, perfect.     The resulting effort sent McCaulley back through his family history, seeking to understand the community that shaped him. In these pages, we meet his great-grandmother Sophia, a tenant farmer born with the gift of prophecy who scraped together a life in Jim Crow Alabama; his mother, Laurie, who raised four kids alone in an era when single Black mothers were demonized as “welfare queens”; and a cast of family, friends, and neighbors who won small victories in a world built to swallow Black lives. With profound honesty and compassion, he raises questions that implicate us all: What does each person’s struggle to build a life teach us about what we owe each other? About what it means to be human?    How Far to the Promised Land is a thrilling and tender epic about being Black in America. It’s a book that questions our too-simple narratives about poverty and upward mobility; a book in which the people normally written out of the American Dream are given voice.